Why is Firefly Oxyluciferin a Notoriously Labile Substance?1. Issue 3 (26th November 2013) - Maltsev, Oleg V.; Nath, Naba K.; Naumov, Panče; Hintermann, Lukas
Abstract The chemistry of firefly bioluminescence is important for numerous applications in biochemistry and analytical chemistry. The emitter of this bioluminescent system, firefly oxyluciferin, is difficult to handle. The cause of its lability was clarified while its synthesis was reinvestigated. A side product was identified and characterized by NMR spectroscopy and X‐ray crystallography. The reason for the lability of oxyluciferin is now ascribed to autodimerization of the coexisting enol and keto forms in a Mannich‐type reaction.